1556 A Prospective Review of Nitrous Oxide Sedation Post Introduction of a Paediatric Procedural Sedation Programme in a Paediatric Emergency Department. (October 2012) - McCoy, S; Barrett, D; Walsh, S; O'sullivan, R
Abstract : Background and Aims: Introduction of a structure Paediatric Procedural Sedation (PPS) Programme facilitates Emergency Department (ED) staff in the safe and efficacious practice of PPS in the ED. Methods: Nitrous oxide was introduced into our institution in July 2011, as part of a PPS programme in the ED. All ED staff (doctors and nurses) must complete the sedation programme before preforming any sedation in the ED. Each sedation event is prospectively recorded on a specific paediatric emergency department sedation checklist and recorded data is then entered into a Microsoft Access® database. Results: Since the programme introduction 82 sedation events have been recorded. The majority of patients were male (49:33 M:F) with an average age of 6 years (17months - 15yrs). The indications for sedation were as follows: Joint manipulation (17), Removal of Foreign Body (12), Suturing (45) and Other (8). We have recorded a total of 17 (20%) adverse events: most commonly, vomiting and agitation. The majority of procedures were performed by ED staff, however some required a specialist to perform the procedure: Plastic Surgery, General Surgery and Orthopedics. Without the provision of sedation in the ED the majority of these patients would have required hospital admission for general anaesthesia. Conclusion: The introduction of nitrous oxide as a sedative agent for procedures in children in our ED has been successful. With low adverse event rates which are comparable to international experience and no serious adverse events have been noted.